Genetic and morphological variation in polymorphic Arctic charr, Salvelinus alpinus, from Icelandic lakes - Gíslason, Daví? (University of Guelph, 1998)
I estimated the morphological and genetic differentiation among sympatric morphs of Arctic charr (Salvelinus alpinus) from five Icelandic lakes. Morphological variation was estimated by measuring fifteen characters while genetic differentiation was estimated by determining allele frequencies at five microsatellite loci. The sympatric morphs showed variable degrees of morphological differentiation. Sympatric morphs clustered together on a Neighbour Joining phenogram based on the frequencies of microsatellite alleles and shared some alleles not found in the charr from other lakes. This suggests that the morphs have diverged in their respective lakes. Furthermore, sympatric morphs from different lakes showed variable degrees of morphological and genetic differentiation. The degree of morphological and genetic differentiation was coupled across lakes, suggesting that morphological differences become more pronounced as reproductive isolation becomes established. These results suggest that resource polymorphism is a diversifying force in speciation.